Photo/electroluminescent properties of novel bipolar oligomers - Kim, OK; Woo, HY; Lee, KS; Kim, JK; Kim, DY; Shim, HK; Kim, CY (ELSEVIER SCIENCE SA, 2001)
Bipolar light-emitting (LE) oligomers consisting of three sequential segments centered by dithienothiophene (DTT) as pi -center and attached by D/D or D/A pair: D-pi -D (dye 1) or D-pi -A (dye 2) where D and A refer to hole transporting (HT) and electron-transporting (ET) units, respectively. Their redox properties are alike, suggesting the resemblance in bipolarity. Photoluminescence (PL) shows that the symmetric D/D system has a higher PL quantum efficiency relative to the D/A system. Electroluminescence (EL) from a single-layer device using a PVK blend displays a slightly higher light intensity with D/A system while EL quantum efficiency of D/D system doubles that of D/A system.